Preparation And Characterization Of Starch-Based Biocomposite Films Reinforced By Dioscorea Hispida Fibers - Salit, Mohd. Sapuan; K.Z., Hazrati; Mohamed Yusoff, Mohd Zuhri; Jumaidin, Ridhwan (Elsevier Editora Ltda, 2021)
In this paper, Dioscorea hispida starch (DHS) biocomposites films were successfully prepared via combining D. hispida starch with sorbitol at different sizes (F1, F2) and concentrations (3, 6, and 9 wt%) D. hispida fiber (DHF) using a film-forming casting technique. Characterization via physical, morphological, mechanical, thermal, and biodegradability was conducted on the films. A significant increment in tensile strength (TS) of the D. hispida starch based films was found with rising fiber content 3–6% and a 9% decrement in concentration. The different sizes and concentrations of D. hispida fiber which were used with 6% small-sized fibers displayed the highest capabilities of increasing the tensile strength and decreasing elongation at break and possessing high value of Young's modulus. The findings demonstrated that tensile strength and Young modulus of the biocomposite films were increased after reinforcement with D. hispida fibers, and the optimal biofiller content was 6%. The biocomposites film revealed a novel waste material, D. hispida fiber, that is eco-friendly and easy to process. It also generates new information on the interactions of different fiber sizes and their effect on the film abilities, which can aid in development of biodegradable materials.